2015
DOI: 10.3390/molecules20059455
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between High-Performance Liquid Chromatography Fingerprints and Uric Acid-Lowering Activities of Cichorium intybus L.

Abstract: This study aimed to explore the spectrum-effect relationships between high-performance liquid chromatography fingerprints and the uric acid-lowering activities of chicory. Chemical fingerprints of chicory samples from ten different sources were determined by high-performance liquid chromatography, and then investigated by similarity analysis and hierarchical clustering analysis. Pharmacodynamics experiments were conducted in animals to obtain the uric acid-lowering activity information of each chicory sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…The evaluation of the levels of total protein and its fractions supply the information required to interpret the occurrence of dehydration under heat stress and inflammatory responses (Bounous, 2000). Zhu et al, (2015) assessed uric acid-lowering activities using high-performance liquid chromatography fingerprints and reported that Cichorium intybus has uric acid-lowering activities. Furthermore, Lin et al, (2014) reported that Cichorium intybus could reduce serum uric acid levels and inhibit liver xanthine dehydrogenase and xanthine oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the levels of total protein and its fractions supply the information required to interpret the occurrence of dehydration under heat stress and inflammatory responses (Bounous, 2000). Zhu et al, (2015) assessed uric acid-lowering activities using high-performance liquid chromatography fingerprints and reported that Cichorium intybus has uric acid-lowering activities. Furthermore, Lin et al, (2014) reported that Cichorium intybus could reduce serum uric acid levels and inhibit liver xanthine dehydrogenase and xanthine oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Various purification procedures of obtained extracts before analysis and (photo)oxidation of polyphenols were also carefully taken into consideration by various researchers (Cefola, Carbone, Minasi, & Pace, 2016;Carazzone et al, 2013;Innocenti et al, 2005;Rossetto et al, 2005). Some authors experimented also lyophilisation technique followed by ultrasonic assisted extraction (UAE) (Sinkovič et al, 2015) or reflux procedures (Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To further identify whether the CSF of the rats treated with EUWE contains CGA, UHPLC-ESI-MS/MS with both positive and negative ion modes were employed to study the fragmentation behaviors of authentic standard of CGA in ESI-MS/MS at first in order to facilitate the structure characterization of the marker constituent. The marker constituent are identified according to their fragmentation data and comparison with the authentic standard from previous studies [33,34]. The ion fragmentations and structure of marker constituent are shown in Figure 7 and Scheme 1.…”
Section: Resultsmentioning
confidence: 99%